2010
DOI: 10.1016/j.ejcts.2010.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplantation using donors 55 years and older: is it safe or just a way out of organ shortage?☆

Abstract: Donor age > or =55 years does not compromise immediate and long-term results after lung transplantation, although long-term observation of patients receiving such an organ suggests earlier lung dysfunction. Due to the rising need of organs, lungs from donors aged 55 or older have to be considered for transplantation. However, the acceptance should be based on donor lung evaluation and individual recipient needs. Long-term outcomes over 5 years need to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…In this context, Pizanis et al, in a series of 19 patients, recently found that an elderly donor (≥55 years) does not affect long-term survival, even when compared with donors under age 55 years. 10 Dezza et al obtained similar results in a series of 10 transplant recipients from donors aged ≥55 years. 11 The most surprising series was that published by the Toronto group.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In this context, Pizanis et al, in a series of 19 patients, recently found that an elderly donor (≥55 years) does not affect long-term survival, even when compared with donors under age 55 years. 10 Dezza et al obtained similar results in a series of 10 transplant recipients from donors aged ≥55 years. 11 The most surprising series was that published by the Toronto group.…”
Section: Discussionsupporting
confidence: 61%
“…6,7 However, up until 5 years ago, very few operations had been performed involving donors over 55 years of age, and the published series all comprised very few cases. 10,11 A review of large lung transplantation series found that the groups with the most extensive patient series often used donors with expanded criteria. The most frequently expanded criteria were smoking (over 20 packs/year) and the presence of radiological anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…158 Similarly, Pizanis et al studied donors and recipients younger or older than 55 years and found no age related significant differences in 186 posttransplant outcomes. 159 Pilcher et al found a statistically significant correlation between donor age and recipient posttransplantation PaO 2 /FiO 2 , but the model fit was poor (R 2 = 0.04), and there was no impact on long-term survival. 160 None of these papers provided COPD specific results.…”
Section: Extended Criteria Donationmentioning
confidence: 99%
“…160 None of these papers provided COPD specific results. [156][157][158][159][160] The Toronto Lung Transplant Program studied the effects of extended donor organs on 467 transplant recipients (129 COPD) during a 12 year experience. Multivariate logistic regression revealed no association between receiving an organ from a donor 60 years of age or older and increased 30-day mortality.…”
Section: Extended Criteria Donationmentioning
confidence: 99%
“…In addition to this unparalleled success in the development of EJCTS [2][3][4][5][6][7][8][9][10], Ludwig von Segesser launched a second publication in September 2002, Interactive CardioVascular and Thoracic Surgery (ICVTS). This interactive Journal is available to the reader in both a printed and an online version.…”
mentioning
confidence: 99%